mz-Compact Spaces (Global Journal of Science Frontier Research, 2014)
In this work we study mz-compact spaces and mz-Lindel of spaces, where m is an infinite cardinal number. Several new properties of them are given. It is proved that every mzcompact space is pseuodocompact (a space on which every real valued continuous function is bounded). Characterizations of mz-compact and mz-Lindel of spaces by multifunctions are given.
Keywords: mz-compact space; mz-Lindel of space; m-compact space; pseudocompact space; realcompact space